2012 45th Hawaii International Conference on System Sciences 2012
DOI: 10.1109/hicss.2012.279
|View full text |Cite
|
Sign up to set email alerts
|

Finding Problems: When Digital Library Users Act as Usability Evaluators

Abstract: Users in digital library usability evaluation typically participate as subjects in studies designed and conducted by usability experts and digital library researchers. What happens however when users take the role of the researchers, and with some basic HCI training, design and conduct their own evaluation of a digital library? For several years, teams of students in master's level HCI classes at Drexel University were given the assignment of designing and carrying out heuristic evaluations of the interface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Users may face difficulties in finding resources (Khoo et al , 2012) or discover that the resources found are not always relevant to their search (Nash, 2005). Moreover, navigation problems may occur when users try to return to a previously accessed record (Jeng, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Users may face difficulties in finding resources (Khoo et al , 2012) or discover that the resources found are not always relevant to their search (Nash, 2005). Moreover, navigation problems may occur when users try to return to a previously accessed record (Jeng, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, Zhang et al (2013) established that a user interface was difficult to use by observing participants searching resources by author. Khoo et al (2012) conducted a usability study on the Internet Public Library (Janes, 1998) digital library by involving users and usability experts, using techniques derived from thinking aloud and eye tracking. As a result of this study, the authors identified some limitations associated with the location of digital resources using their interfaces, as users expressed frustration with the high number of imprecise results obtained from the previously defined search criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research found that these interfaces do not meet all the needs of users (Tenopir, 2003). Users through interfaces, have difficulty finding resources (Khoo, Kusunoki, & MacDonald, 2012), and the resources discovered are not always relevant to search (Nash, 2005). Navigation problems appear when returning to previously accessed registries (Jeng, 2005).…”
Section: Previous Effort In the Fieldmentioning
confidence: 99%
“…There are different types of techniques used in data visualization, but for our purposes of study, we performed a selection of techniques according to: i) graphical representations structures (Schulz, Hadlak, & Schumann, 2011), ii) thematic clustering strategies (Shneiderman, Feldman, Rose, & Grau, 2000), and finally iii) through hierarchical representations of categories (Khoo, Kusunoki, & MacDonald, 2012;Tenopir, 2003).…”
Section: Visualization Techniquesmentioning
confidence: 99%